المواءمة الأفقية في إدارة الموارد البشرية: دراسة تطبيقية على عملية تقييم الأداء وتحديد الإحتياجات التدريبية في البنوك التجارية السعودية - الزهراني، عبدالله بن عطية بن عبدالله (المنظمة العربية للتنمية الإدارية, 2015)
This study aims to investigate the level of applying the horizontal fit between performance appraisals and training needs in Saudi commercial banks. Population consisted of (12) commercial banks working at KSA, from which a sample drawn represented HR managers working at (10) of these banks. A questionnaire developed by the researcher submitted to subject (88) managers. The most salient findings of the study are: Most activities of performance appraisal and training needs are applicable at moderate level according to the more developed practices in the selected sample. The horizontal fit between performance appraisal and training needs are applicable at the minimum level of an average degree by the selected sample. There are many barriers preventing Saudi commercial banks from adapting the horizontal fit between performance appraisal and training needs. Education level, years of experience and bank’s size play a significant impact on determining the level of applying the horizontal fit between performance appraisals and training needs. Finally, the study reveals a set of recommendations, the most important is encouraging Saudi commercial banks to adapt the horizontal fit between their performance appraisal and training needs system, and make efforts to minimize its barriers.
Keywords: السياسة المالية -- النظام المالي -- الأجهزة المصرفية -- البنوك التجارية السعودية -- الموارد البشرية